Friendship ties and geographical mobility: evidence from the BHPS - Michèle Belot; John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2006)
A common finding in analyses of geographic mobility is a strong association between past movement and current mobility, a phenomenon that has given rise to the so called mover-stayer model. We argue in this paper that one of the driving forces behind this heterogeneity is the strength of local social ties. We use data from the BHPS on the location of the three closest friends and the frequency of contacts. We estimate the processes of friendship formation and residential mobility jointly, allowing for correlation between the two processes. Our results show that the location of the closest friends matters substantially in the mobility decision, and matters more than the frequency of contacts.
Keywords: 330